Drug Resistant Cases of tuberculosis in Directly Observed Treatment Short Course - Shrestha, B; Bhatt, A B; Bhatta, C P (Journal of Nepal Health Research Council, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: Resistance of Mycobacterium tuberculosis to antituberculous drugs has emerged as a major public health threat. The objective of this study was to determine Multi Drug Resistance cases of tuberculosis in Directly Observed Treatment Short Course program of Nepal. Methods: The sputum samples collected and culture on Lowenstein Jensen media followed by biochemical test. All the isolates antibiotic sensitivity test performed on medium by proportion method. Results: Tuberculosis was most commonly found in economically active age group (21-50 years). All the isolates of pulmonary tuberculosis were found to be M. tuberculosis. A Multi-drug resistant case of tuberculosis primary and acquired in Directly Observed Treatment Short Course Program of Nepal was found (3.6%). Out of 460 untreated cases, 9 (1.9%) cases were found to be MDR and among 90 previously treated cases 11 (12.2%) were found to be MDR. Multi drug resistant cases of tuberculosis were found most commonly in productive age group (21-30). The incidence of tuberculosis was found higher in male than in female. But multi drug resistant M. tuberculosis cases equally affected both the gender. Majority of the MDR cases found higher number of M. tuberculosis in their sputum. Conclusions: The above study showed that drug resistant cases of tuberculosis in DOTS program of Nepal was found higher. To reduce the drug resistance, before starting chemotherapy antibiotic sensitivity test should be performed. Key words: granuloma,histopathology, leprosy, Ridley-Jopling classification, tuberculoid